Lignite Upgradation of Mae Moh Power Plant Thailand via Low – Temperature Pyrolysis - Thant, Yin May; Malik, Fawad Rahim; Chaichana, Chatchawan (International Journal on Food, Agriculture and Natural Resources, 2023)
The lignite at Mae Mo mine in Lampang Thailand, which is the focus of this study is ranked as the lowest class in coal classification. The lignite is currently burned directly in boilers for electricity production, resulting in inefficiencies. The objective is to use low-temperature pyrolysis to improve the lignite. Lab-scale experiments were conducted using different lignite particle sizes (2.36 mm, 1.00 mm, and 0.25 mm) at temperatures ranging from 250-600°C and retention times of 0-60 mins. The best quality lignite was achieved processing a particle size of 2.36 mm at a temperature of 350°C and a retention time of 20 mins. The gross calorific value, fixed carbon, and char content increased with higher operating temperatures. Weight loss occurred between 300-600°C due to the degradation of volatile organic fractions and char formation. Ash and sulfur constituents increased in smaller coal sizes. The average gross calorific value of char was 23.04-27.19 MJ/kg. Lower operating temperatures, larger coal sizes, and sufficient retention time are recommended for the pyrolysis process to achieve optimal results.